Impact of behavioral factors towards the adoption of mobile learning among higher education students in public and private universities: A pitch - Haroon Iqbal; Hafiz Ahmad Ashraf (Journal of Accounting and Management Information Systems (JAMIS), 2017)
This pitch research letter (PRL) applies the pitch template developed by Faff (2015, 2017) to an academic project on the impact of behavioral factors towards the adoption of mobile learning among higher education students in public and private universities of Pakistan. This template is helpful in identifying the core elements of the proposed research project. This PRL consists of a brief introduction about the pitch, followed by a brief commentary on the pitch and personal reflections of the pitcher on the pitch exercise itself.
Keywords: I23; 650; Pitching research; Mobile learning; Higher education; Pakistan